2017
DOI: 10.3389/fpls.2017.00395
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of Snf1-Related Protein Kinase2 (SnRK2) and Calcium Sensor (SCS) Gene Lineages, and Dimerization of Rice Homologs, Suggest Deep Biochemical Conservation across Angiosperms

Abstract: Members of the sucrose non-fermenting related kinase Group2 (SnRK2) subclasses are implicated in both direct and indirect abscisic acid (ABA) response pathways. We have used phylogenetic, biochemical, and transient in vivo approaches to examine interactions between Triticum tauschii protein kinase 1 (TtPK1) and an interacting protein, Oryza sativa SnRK2-calcium sensor (OsSCS1). Given that TtPK1 has 100% identity with its rice ortholog, osmotic stress/ABA-activated protein kinase (OsSAPK2), we hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…SAPK1 and SAPK3 are activated by osmotic stress [39,40]. SAPK4 is weakly activated by ABA and osmotic stress, and SAPK10 is strongly activated by ABA and osmotic stress [41]. Abscisic acid (ABA) plays an important role in the drought resistance of plants.…”
Section: Discussionmentioning
confidence: 99%
“…SAPK1 and SAPK3 are activated by osmotic stress [39,40]. SAPK4 is weakly activated by ABA and osmotic stress, and SAPK10 is strongly activated by ABA and osmotic stress [41]. Abscisic acid (ABA) plays an important role in the drought resistance of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we cannot exclude that AtSCS-A also inhibits the ABA-nonresponsive SnRK2s, because AtSCS-A in contrast to AtSCS-B interacts not only with the ABA-activated SnRK2s but also with the kinases of group 1, which are not activated by ABA. However, the evolution studies performed by Holappa et al (2017) have shown that SCS proteins appeared in the earliest land plants at about the same time as the ABA receptors Regulatory Component of ABA Receptor/Pyrabactin Resistance1/PYR1-like, PP2Cs, and ABA-activated SnRK2s (from group 3) that constitute the prototype of the SnRK2 family Komatsu et al, 2013;Shinozawa et al, 2019). The ABA-nonresponsive SnRK2s evolved later, in vascular plants.…”
Section: Discussionmentioning
confidence: 99%
“…Still we cannot exclude that AtSCS-A also inhibits the ABA-non-responsive SnRK2s, since AtSCS-A in contrast to AtSCS-B interacts not only with the ABA-activated SnRK2s but also with kinases of the group 1, which are not activated by ABA. However, the evolution studies performed by Holappa et al (2017) have shown that SCS proteins appeared in earliest land plants at about the same time as ABA receptors - RCAR/PYR/PYL (RCAR, Regulatory Component of ABA Receptor/PYR1, Pyrabactin Resistance 1/PYL, PYR1-like), PP2Cs (Umezawa et al, 2010; Komatsu et al, 2013; Shinozawa et al, 2019), and ABA-activated SnRK2s (from group 3) that constitute the prototype of the SnRK2 family. The ABA-non-responsive SnRK2s evolved later, in vascular plants.…”
Section: Discussionmentioning
confidence: 99%